2012
DOI: 10.2355/isijinternational.52.1894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Addition of Cr, Mo and Ni on the Microstructure and Retained Austenite Characteristics of 0.2% C^|^ndash;Si^|^ndash;Mn^|^ndash;Nb Ultrahigh-strength TRIP-aided Bainitic Ferrite Steels

Abstract: Cr, Mo and/or Ni were added to TRIP-aided bainitic ferrite (TBF) steel (0.2% C, 1.5% Si, 1.5% Mn and 0.05% Nb ultrahigh-strength TBF steel) in order to increase its hardenability. In addition, the effects of the alloying elements on the Vickers hardness, microstructure and retained austenite characteristics of the TBF steels were investigated. When the TBF steels were austempered at temperatures between MS and Mf, the Vickers hardness increased from HV300 to HV430 with increasing hardenability. The microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 16 publications
0
24
2
Order By: Relevance
“…The authors' previous study [18] also reported that Cr addition improves the comprehensive property of the steel austempered at 350 • C. However, the present study finds that at a lower transformation temperature (400 • C), Cr addition increases the comprehensive property of the steel, whereas Cr addition decreases the comprehensive property of the steel at higher transformation temperatures (430 • C and 450 • C). The difference between the previous result [18,27,28] and the present result may be because the austempering temperatures used in previous studies are relatively lower. In addition, the effect of Cr on bainitic transformation was not studied in references [27,28].…”
Section: Dilatationcontrasting
confidence: 93%
See 2 more Smart Citations
“…The authors' previous study [18] also reported that Cr addition improves the comprehensive property of the steel austempered at 350 • C. However, the present study finds that at a lower transformation temperature (400 • C), Cr addition increases the comprehensive property of the steel, whereas Cr addition decreases the comprehensive property of the steel at higher transformation temperatures (430 • C and 450 • C). The difference between the previous result [18,27,28] and the present result may be because the austempering temperatures used in previous studies are relatively lower. In addition, the effect of Cr on bainitic transformation was not studied in references [27,28].…”
Section: Dilatationcontrasting
confidence: 93%
“…The difference between the previous result [18,27,28] and the present result may be because the austempering temperatures used in previous studies are relatively lower. In addition, the effect of Cr on bainitic transformation was not studied in references [27,28]. The authors' previous study [18] reported that Cr addition increases the amount of isothermal bainitic transformation at 350 • C, because high temperature ferritic transformation occurs in Cr-free steel and consumes some untransformed austenite before austempering, whereas no ferritic transformation occurs in Cr-added steel.…”
Section: Dilatationcontrasting
confidence: 93%
See 1 more Smart Citation
“…On further increasing cooling rate to 110 Ks -1 , the Bs increased again up to 631 °C. It corresponds to observations by other researchers [33,35]. Bs and martensite transformation start temperature Ks -1 .…”
Section: Continuous Cooling Transformation Diagrammentioning
confidence: 99%
“…TBF steel is produced by an isothermal transformation (IT) process at temperatures higher than the martensite transformation-start temperature (Ms) (when the matrix structure is bainitic ferrite) or between Ms and the martensite transformation-finish temperature (Mf) temperature (when the matrix structure is a mixture of bainitic ferrite and martensite) after austenitizing. 2,3) Q&P steel is fabricated by first quenching the steel at a temperature below Ms after austenitizing and then by partitioning (P) at a temperature higher than Ms (the matrix structure is the same mixture of bainitic ferrite and martensite as in the case of TBF steel). [4][5][6] In order to increase the strength of TBF steel, Sugimoto et al recently developed a C-Si-Mn "TRIP-aided martensitic" (TM) steel with a wide lath-martensite structure and a narrow lath-martensite/metastable austenite-retained complex phase (MA-like phase).…”
Section: Introductionmentioning
confidence: 99%